Digital Diplomacy: The Influence of Social Media in Forming a Country's Image in the Era of Globalization - Putu Maha Putra (Pt. Anagata Sembagi Education, 2024)
The rapid development of information and communication technology has had a significant impact on international relations, affecting various aspects such as diplomacy, trade, and cybersecurity. Social media as a strategic tool in digital diplomacy allows countries to shape and promote their global image. This study examines the role of social media in shaping a country's image in the international arena, focusing on the intensity and diversity of its use, as well as the interaction between social media content and public perception. Through a quantitative approach, this study analyzed 290 social media accounts from major cities in Indonesia, exploring how their content influences the country's global image. The results show that the frequency and type of social media content ranging from public services, tourism, to cultural and economic promotion are important factors in shaping a positive national image. In addition, there is a strong positive relationship between the intensity of social media use and public perception of the country's image, with significant influences on the economic, political, and cultural dimensions. This study provides valuable insights into how digital communication strategies can be utilized to improve a country's international position..